The Quaternary La Garrotxa volcanic field (NE of Iberia): A geochronological approach - Joan Martí; Julia Ricci; Llorenç Planagumà; Gerardo J. Aguirre Díaz (Quaternary Science Advances)
Monogenetic volcanic fields exhibit extended periods of magmatic activity, often spanning several million to tens of millions of years. Understanding the evolution of this activity is challenging due to incomplete geological records and limited geochronological data. However, the relative volcanic stratigraphy and morphometric analysis of volcanic landforms enable the identification of temporal patterns in volcanic activity. These patterns often reveal clusters of eruptions interspersed with periods of relative inactivity, reflecting the tectonic evolution of the region, which influences magma generation and ascent.Quantifying this temporal evolution is crucial for Quaternary monogenetic fields, as their activity may still be ongoing, posing potential risks. This is exemplified by the La Garrotxa volcanic field in the Catalan Volcanic Zone, part of the European Rift System, active from the mid-Pleistocene to the early Holocene. In this study, we present 15 new Ar-Ar ages, along with a comprehensive field review, to accurately establish the recent temporal evolution of this volcanic field, refining previous stratigraphies based solely on field relations and morphometric analysis. These new ages indicate that volcanic activity in the La Garrotxa Volcanic Field is more recent and frequent than previously believed, with significant implications for volcanic hazard assessment.